Mono-layer films with superior barrier properties and full recyclability: The system of Poly(ethylene terephthalate)/Poly(glycolic acid). (16th January 2023) - Shao, Hanghang; Niu, Deyu; Liu, Bo; Xu, Pengwu; Yang, Weijun; Lemstra, Piet Jan; Bastiaansen, Cees W.M.; Wang, Zhenyu; Wang, Chuanxi; Ma, Piming
Abstract: In the area of food packaging, multilayer films are widely used to prevent the penetration of O2, CO2 and H2 O (vapor), but these multilayer films cannot be recycled and re-used. In a series of papers, we will discuss the development of mono-layer barrier films with high barrier properties. Transparent mono-layer barrier films were made based on blends of poly(ethylene terephthalate) (PET, ≥80 wt%) and poly(glycolic acid) (PGA, ≤20 wt%, a well-known high barrier polymer) using simultaneous biaxial stretching process. The morphology of the PGA phase was transferred from a spherical structure into an oriented lamellar structure upon solid state stretching, which increased the tortuous path of gas molecules. As a result, the oxygen permeability (OP) of PET was decreased by 90 ± 2.2% after incorporation of the PGA and biaxial stretching (3 × 3). The tensile strength and Young's modulus were increased, with good toughness (elongation at break about 40%) and high transmittance ( T > 80%). Apparently, this work provides a feasible method for preparing recyclable, transparent and high-end barrier mono-layer PET films with a minor content of a second polymer (PGA), and the experimental findings are expected to be applicable to other systems and will be discussed in subsequent papers. Graphical abstract: Image 1 Highlights: Biaxial stretching leads to significant structural evolution of PET/PGA blends. The dispersed PGA phase evolves from spherical structure to lamellar structure by biaxial stretching. PGA phase with lamellar structure improves oxygen barrier properties. The tensile properties of biaxially oriented films steadily improve with increasing the draw ratio. Mono-layer barrier films can be recycled and reproduced.